Bridging the Gap Between Theory and Practice in the Vehicle Routing Research - HOSNY, Manar (International Journal of Applied Methods in Electronics and Computers, 2014)
Research studying effective planning and optimization in the vehicle routing field has increased tremendously in the last few decades. Advances in technology and computational power have encouraged researchers to consider various vehicle routing problem types and constraints, and to experiment with new algorithmic techniques that can be applied for the automation of vehicle planning. Despite this, research in the vehicle routing domain is often accused of being too idealistic. Given the difficulty of solving vehicle routing problems, many simplifying assumption are being incorporated into problem solving techniques, in order to make the solution approach more manageable. In this paper we discuss some real life constraints that the research community should be aware of when addressing vehicle routing problems. We highlight how theoretical research in this area can be integrated into commercially applicable software. An overview of future trends in scientific research tackling this issue is also provided. This paper tries to give an insight into how developing richer vehicle routing models can help in realistic settings to improve logistic planning.